Jatropha curcas L. and J. macrocarpa Griseb: seed morphology, viability, dormancy, germination and growth of seedlings - Tavecchio, Nancy E. de las M.; Vigliocco, Ana Edit; Terenti, Oscar Antonio; Wassner, Diego; Reinoso, Herminda E.; Pedranzani, Hilda E. (Scientific Research, 2018)
To achieve a good production of a crop, it is essential to know the ability of the species to successfully complete two critical stages in the life cycle such as germination and seedling establishment. In this paper we study in comparative form structure of the seed, the importance of tegument in dormancy, the effect of accelerated aging on seed germination and viability, and the early and late growth in J. curcas and J. macrocarpa. External morphology of the seeds allow difference and internally also the embryos show evident differences. J. macrocarpa germination is around 0% - 4%. The total removal of tegument showed a 50% increase and the other treatments between 0% - 10%. Aging accelerated by Tetrazolium test allowed a comparative analysis of VP and GP. J. curcas maintains both to 96 h, while J. macrocarpa the seed viability is registered along the all treatment. J. macrocarpa seeds have less synchronicity than those of J. curcas. ABA and JAs were detected in tegument of J. macrocarpa and J. curcas seeds. JA could have a roll in inhibition of germination of J. macrocarpa seeds. Early and late growth, FW and DW of root, hypocotyl, epicotyl and leaf of J. curcas were significantly different in both species.